Effect of nano TiO2 & ZnO on the hydration properties of Portland cement. (2022) - Goyal, Raju; Verma, Vinay K.; Singh, N.B.
Abstract: When water is added to cement, complex hydration reactions with the evolution of heat occur. The hydration of cement has been studied by using a number of techniques such as calorimetry, X-ray diffraction, setting time, compressive strength, thermal method, and scanning electron microscopy. In the presence of nano TiO2 and ZnO, the hydration properties of cement are changed. Results have shown that nano ZnO has retarding effect, whereas nano TiO2 has an accelerating effect to a greater extent. Attempts have been made to understand the role of nanomaterials during the hydration of cement.